A core-shell structure double-max phase high-temperature strengthening TiAl-based composite material and a preparation method thereof
Patent Information
- Application Number
- CN202410128293.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-30
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2044-01-30
AI Technical Summary
然而,采用真空热压烧结、热等静压、放电等离子烧结等粉末冶金烧结工艺直接制备的TiAl基复合材料坯锭往往还存在少量微孔(大部分为粉末缺陷导致)以及晶界平直等不足,影响增强相强化效果的充分发挥
[0020]1、本发明利用C原子和Si原子在基体合金中溶解度不同,以及合金元素在不同MAX相中溶解度不同,制备出具有核壳结构的双MAX相高温强化TiAl基复合材料。在热压烧结过程中,SiC颗粒中的Si和C元素发生了分离,其中C元素从增强相内部向基体呈现由高到底的梯度分布,而Si元素则主要富集在增强相的外层。本发明实现了在TiAl基复合材料中引入具有核壳结构的双MAX相,能够有效提高TiAl基合金的高温强度。
Smart Images

Figure CN118186253B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of alloy materials technology, specifically to a core-shell structured dual MAX phase high-temperature reinforced TiAl-based composite material and its preparation method. Background Technology
[0002] TiAl-based alloys have low density (~4.0 g / cm³). 3 TiAl-based alloys possess excellent comprehensive properties, including high specific strength, high specific modulus, good high-temperature oxidation resistance, and creep resistance, making them considered the most promising advanced high-temperature structural materials for applications in the 700–1000℃ range. While TiAl-based alloys have achieved initial engineering applications in industrial fields such as aero-engines—for example, GE uses them to manufacture low-pressure turbine blades for its GEnx and GE9X aero-engines—widespread application is still some way off. Room-temperature brittleness, difficulty in further improving high-temperature strength, and poor formability are the main reasons for this situation. Among these, how to further improve their high-temperature strength has become one of the most pressing fundamental problems to be solved. Research shows that using composite material technology is one of the effective ways to improve the comprehensive mechanical properties of TiAl-based alloys. Using composite material technology, employing continuous fiber reinforcement or discontinuous short fibers, whiskers, and particles to reinforce TiAl-based alloys and obtain TiAl-based composite materials with excellent comprehensive properties has become the main trend in the development of TiAl-based alloys.
[0003] The preparation processes of TiAl-based composite materials mainly include melting and casting and powder metallurgy. Melting and casting was the earliest method used to prepare TiAl alloys and their composites, offering advantages such as near-net-shape forming, simple process, and low cost. However, it also suffers from disadvantages such as coarse microstructure and susceptibility to casting defects like component segregation, shrinkage cavities, porosity, and cracks. Powder metallurgy effectively avoids casting defects such as porosity and shrinkage cavities. TiAl-based alloys and composites prepared using this method have uniform composition and fine microstructure, which is beneficial for obtaining superior mechanical properties. Therefore, powder metallurgy has become a very important method for preparing TiAl alloys and composites. However, TiAl-based composite ingots directly prepared using powder metallurgy sintering processes such as vacuum hot pressing, hot isostatic pressing, and spark plasma sintering often still have a small number of micropores (mostly caused by powder defects) and straight grain boundaries, affecting the full realization of the strengthening effect of the reinforcing phase.
[0004] MAX phase is a ternary layered compound whose composition can be represented by M n+1 AX n In this representation, M is a transition metal, A is mainly a group IIIA and IVA element, X is a C or N element, and n generally takes a value between 1 and 3. Common compounds include Ti₂AlC, Ti₂AlN, and Ti₃SiC. 2、Ti3AlC2 and Ti3GeC2, among others. MAX phases possess characteristics of both metals and ceramics: they exhibit metal-like thermal conductivity, electrical conductivity, and machinability, while also possessing ceramic-like high melting point, high hardness, high modulus, high oxidation resistance, and thermal stability. Therefore, preparing MAX phase-reinforced TiAl-based composites can effectively improve the high-temperature strength and other properties of TiAl alloys, showing promising application prospects. Summary of the Invention
[0005] To overcome the shortcomings of existing technologies, this invention provides a core-shell structured dual-MAX phase high-temperature reinforced TiAl-based composite material and its preparation method. This method utilizes the different solubilities of C and Si atoms in the matrix alloy, as well as the different solubilities of alloying elements in different MAX phases, to prepare a core-shell structured dual-MAX phase high-temperature reinforced TiAl-based composite material.
[0006] To achieve the above objectives, the present invention provides a core-shell structure dual MAX phase high-temperature reinforced TiAl-based composite material, wherein: the matrix of the TiAl-based composite material includes a γ phase, and the core-shell structure reinforcing phase includes an inner Ti2AlC phase and an outer Ti3SiC2 phase.
[0007] Preferably, the size of the core-shell structure reinforcing phase is 10–50 μm, wherein the thickness of the outer Ti3SiC2 phase is 0.5–3 μm.
[0008] Preferably, the raw materials for the TiAl-based composite material include TiAl alloy powder and SiC powder; the SiC powder accounts for 1 to 5 wt% of the mass fraction of the raw materials for the TiAl-based composite material.
[0009] Preferably, in the TiAl alloy, by atomic percentage, Al: 43-48%; Nb: 2-10%; Cr: 0-4%; W: 0-2%; B: 0-0.5%, with the remainder being Ti.
[0010] This invention provides a method for preparing a core-shell structured dual MAX phase high-temperature reinforced TiAl-based composite material, which includes the following steps:
[0011] Ball milling: SiC powder and TiAl alloy powder are ball milled to obtain a mixed powder;
[0012] Hot pressing sintering: The mixed powders are hot pressed and sintered to obtain a TiAl-based composite material preform;
[0013] Encased hot forging: hot forging the billet by encasing it in a sleeve;
[0014] Heat treatment: The cladding body is subjected to annealing heat treatment, followed by furnace cooling.
[0015] Preferably, the ball milling is carried out under argon protection, with a ball-to-powder ratio of 1:5, and the grinding balls are made of stainless steel.
[0016] Preferably, the hot pressing sintering is carried out under an argon atmosphere, at a temperature of 1250–1300°C, a holding time of 2–5 hours, and a pressure of 20–50 MPa.
[0017] Preferably, the hot forging temperature of the sheath is 1250–1300°C, and the deformation is 30%–70%.
[0018] Preferably, the heat treatment is to hold at 800-1000°C for 2 hours.
[0019] The beneficial effects of this invention are as follows:
[0020] 1. This invention utilizes the different solubilities of C and Si atoms in the matrix alloy, as well as the different solubilities of alloying elements in different MAX phases, to prepare a core-shell structured dual-MAX phase high-temperature reinforced TiAl-based composite material. During hot-pressing sintering, Si and C elements in the SiC particles separate, with C exhibiting a gradient distribution from high to low from the interior of the reinforcing phase towards the matrix, while Si elements are mainly enriched in the outer layer of the reinforcing phase. This invention achieves the introduction of a core-shell structured dual-MAX phase into TiAl-based composite materials, effectively improving the high-temperature strength of TiAl-based alloys.
[0021] 2. This invention utilizes hot-pressing sintering to generate a dual MAX phase with a core-shell structure in a TiAl alloy matrix. On one hand, the formation of the outer Ti3SiC2 phase effectively hinders element diffusion between the TiAl matrix and the inner Ti2AlC phase. Therefore, this core-shell structure exhibits higher thermal stability compared to a single MAX phase. On the other hand, the hardness of the outer Ti3SiC2 phase is often higher than that of the inner Ti2AlC phase. This "hard on the outside, soft on the inside" core-shell structure provides better strength and toughness compared to a single phase, thereby suppressing crack formation during loading. Therefore, this core-shell structure offers better strengthening and toughening effects compared to a single MAX phase.
[0022] 3. The present invention can adjust the amount and distribution of the double MAX phase by controlling the SiC addition amount, hot pressing sintering and hot forging process parameters. It is flexible and convenient, the whole process is simple to operate and easy to implement, which improves the application value of the method of the present invention. Attached Figure Description
[0023] Figure 1 Low-magnification SEM microstructure of core-shell structured dual MAX phase high-temperature reinforced Ti-47.5Al-7Nb-0.4W-0.1B matrix composite material;
[0024] Figure 2Electron probe microanalysis of the reinforced phase of the prepared composite material was performed, including: (a) backscattered microstructure; (b) Ti elemental distribution; (c) Al elemental distribution; (d) Nb elemental distribution; (e) W elemental distribution; (f) B elemental distribution; (g) Si elemental distribution; and (h) C elemental distribution. Detailed Implementation
[0025] To better illustrate the purpose, technical solution, and advantages of this invention, the following will provide further explanation of this application in conjunction with specific embodiments.
[0026] The technical solution adopted in this invention is:
[0027] In a first aspect, the present invention provides a method for preparing a core-shell structured dual MAX phase high-temperature reinforced TiAl-based composite material. The method is as follows: SiC and TiAl-based alloy powders are mixed in a certain proportion and then mechanically ball-milled to obtain a mixed powder. The mixed powder is then hot-pressed and sintered under argon atmosphere protection to obtain a TiAl-based composite material blank. Finally, the TiAl-based alloy composite material blank is subjected to a certain amount of deformation and hot-forging. After cooling, the desired core-shell structured dual MAX phase high-temperature reinforced TiAl-based composite material is obtained.
[0028] Preferably, the composition of the TiAl alloy powder, by atomic percentage, is Al: 43-48%; Nb: 2-10%; Cr: 0-4%; W: 0-2%; B: 0-0.5%, with the remainder being Ti.
[0029] Preferably, the mass fraction of SiC in the mixed powder is 1-5 wt%.
[0030] Preferably, during the mechanical ball milling process, the powder is mixed under argon protection, the ball-to-powder ratio is 1:5, and the grinding balls are made of stainless steel.
[0031] Preferably, the argon atmosphere-protected hot pressing sintering temperature is 1250-1300℃, the holding time is 2-5h, and the pressure is 20-50MPa.
[0032] Preferably, the hot forging temperature of the cladding is 1250-1300℃, the deformation is 30%-70%, and after hot forging, the cladding body is subjected to annealing heat treatment. The specific heat treatment process is: holding at 800-1000℃ for 2 hours, and then furnace cooling.
[0033] In a second aspect, the present invention provides a core-shell structured dual MAX phase high-temperature reinforced TiAl-based composite material obtained by the preparation method according to any of the schemes in the first aspect above. The matrix of the composite material is a near-γ structure, mainly composed of γ phase, while the uniformly distributed core-shell structured reinforcing phase is mainly composed of internal Ti2AlC phase and outer Ti3SiC2 phase.
[0034] Preferably, the size of the core-shell structured reinforcing phase is 10–50 μm, wherein the thickness of the outer Ti3SiC2 phase is 0.5–3 μm.
[0035] Example 1
[0036] In this embodiment, the preparation method of the core-shell structured dual-MAX phase high-temperature reinforced TiAl-based composite material is as follows: 3g of SiC powder and 97g of Ti-47.5Al-7Nb-0.4W-0.1B (at.%) alloy powder are placed in a ball mill jar and mechanically ball-milled at 150 r / min for 7.5 h at a ball-to-powder ratio of 1:5 to obtain a mixed powder. The mixed powder is then hot-pressed and sintered in an argon atmosphere at 1250℃ and 20MPa for 2 h to obtain a TiAl-based composite material blank. The blank is then hot-forged in a cladding at 1250℃ with a deformation of 50%. After hot forging, the cladding body is subjected to annealing heat treatment. The specific heat treatment process is: holding at 850℃ for 2 h, followed by furnace cooling, to obtain the core-shell structured dual-MAX phase high-temperature reinforced Ti-47.5Al-7Nb-0.4W-0.1B-based composite material.
[0037] Figure 1 This is a low-magnification SEM micrograph of the core-shell structured dual-MAX phase high-temperature reinforced Ti-47.5Al-7Nb-0.4W-0.1B-based composite material prepared in this embodiment. From... Figure 1 It can be seen that the matrix of the composite material is a near-γ structure, and the reinforcing phase exhibits a significant core-shell structure with a size of 10–50 μm.
[0038] Figure 2 The results are from electron probe microanalysis of the reinforcing phase in the composite material. Figure 2 It can be clearly seen that in the composite material prepared in this embodiment, the three elements Ti, Al and C are mainly distributed in the Ti2AlC phase of the reinforcing phase, while other elements are mainly enriched in the outer Ti3SiC2 phase of the reinforcing phase, and the thickness of the outer Ti3SiC2 phase is 0.5 to 3 μm.
[0039] The high-temperature compressive yield strength is as follows: the yield strength at 900℃ can reach more than 400MPa, compared with the TiAl matrix alloy at 900℃, which is only 370MPa; the yield strength at 1000℃ can reach more than 230MPa, compared with the TiAl matrix alloy at 1000℃, which is only 200MPa.
[0040] Example 2:
[0041] In this embodiment, the preparation method of the core-shell structured dual-MAX phase high-temperature reinforced TiAl-based composite material is as follows: 1g of SiC powder and 99g of Ti-48Al-2Cr-2Nb alloy powder are placed in a ball mill jar and mechanically ball-milled at 150r / min for 7.5h at a ball-to-powder ratio of 1:5 to obtain a mixed powder. The mixed powder is then hot-pressed and sintered in an argon atmosphere at 1300℃ and 20MPa for 3h to obtain a TiAl-based composite material blank. The blank is then hot-forged in a cladding at 1250℃ with a deformation of 40%. After hot forging, the cladding body is subjected to annealing heat treatment. The specific heat treatment process is: holding at 900℃ for 2h, followed by furnace cooling, to obtain the core-shell structured dual-MAX phase high-temperature reinforced Ti-48Al-2Cr-2Nb-based composite material.
[0042] Similarly, the matrix of the composite material obtained in this embodiment is a near-γ structure, mainly composed of γ phase, while the uniformly distributed core-shell structure reinforcing phase is mainly composed of internal Ti2AlC phase and outer Ti3SiC2 phase.
[0043] The high-temperature compressive yield strength is as follows: the yield strength at 900℃ can reach more than 350MPa, compared with the TiAl matrix alloy at 900℃, which is only 300MPa; the yield strength at 1000℃ can reach more than 190MPa, compared with the TiAl matrix alloy at 1000℃, which is only about 150MPa.
[0044] Example 3:
[0045] In this embodiment, the preparation method of the core-shell structured dual MAX phase high-temperature reinforced TiAl-based composite material is as follows: 4g of SiC powder and 96g of Ti-48Al-2Cr-2Nb alloy powder are placed in a ball mill jar and mechanically ball-milled at 150 r / min for 7.5 h at a ball-to-powder ratio of 1:5 to obtain a mixed powder. The mixed powder is then hot-pressed and sintered under argon atmosphere at 1280℃ and 30MPa for 2.5 h to obtain a TiAl-based composite material blank. The blank is then hot-forged in a cladding at 1300℃ with a deformation of 60%. After hot forging, the cladding body is subjected to annealing heat treatment. The specific heat treatment process is: holding at 950℃ for 2 h, followed by furnace cooling, to obtain the core-shell structured dual MAX phase high-temperature reinforced Ti-48Al-2Cr-2Nb-based composite material.
[0046] Similarly, the matrix of the composite material obtained in this embodiment is a near-γ structure, mainly composed of γ phase, while the uniformly distributed core-shell structure reinforcing phase is mainly composed of internal Ti2AlC phase and outer Ti3SiC2 phase.
[0047] The high-temperature compressive yield strength is as follows: the yield strength at 900℃ can reach more than 380MPa, compared with the TiAl matrix alloy at 900℃, which is only 300MPa; the yield strength at 1000℃ can reach more than 210MPa, compared with the TiAl matrix alloy at 1000℃, which is only about 150MPa.
[0048] In the TiAl-based composite material of this invention, Si is mainly distributed in the outer phase of the core-shell reinforcing phase, while C is mainly distributed in the inner phase. During hot-pressing sintering, Si and C elements in the SiC particles separate, with C exhibiting a gradient distribution from the interior of the reinforcing phase to the matrix, while Si is mainly enriched in the outer layer of the reinforcing phase. This phenomenon may be caused by two factors: firstly, Si atoms have very low solubility in the TiAl matrix, thus they cannot diffuse into the matrix on a large scale during hot-pressing sintering, resulting in enrichment on the surface of the reinforcing phase; secondly, Si has very low solubility in the Ti2AlC phase, therefore it tends to be distributed on the exterior of the reinforcing phase. This invention introduces a core-shell dual MAX phase into the TiAl-based composite material, which can effectively improve the high-temperature strength of the TiAl-based alloy.
[0049] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the essence and scope of the technical solutions of the present invention.
Claims
1. A core-shell structured dual-MAX phase high-temperature reinforced TiAl-based composite material, characterized in that: The matrix of the TiAl-based composite material includes a γ phase, and the core-shell structure reinforcing phase includes an inner Ti2AlC phase and an outer Ti3SiC2 phase.
2. The core-shell structured dual-MAX phase high-temperature strengthened TiAl-based composite material according to claim 1, characterized in that: The core-shell structure reinforcement phase has a size of 10–50 μm, with the outer Ti3SiC2 phase having a thickness of 0.5–3 μm.
3. The core-shell structured dual-MAX phase high-temperature strengthened TiAl-based composite material according to claim 1, characterized in that: The raw materials of the TiAl-based composite material include TiAl alloy powder and SiC powder, wherein the SiC accounts for 1 to 5 wt% of the raw materials of the TiAl-based composite material.
4. The core-shell structured dual-MAX phase high-temperature strengthened TiAl-based composite material according to claim 3, characterized in that: The TiAl alloy contains, by atomic percentage, Al: 43-48%; Nb: 2-10%; Cr: 0-4%. W:0~2%; B: 0-0.5%, the remainder is Ti.
5. A method for preparing the core-shell structured dual MAX phase high-temperature reinforced TiAl-based composite material according to any one of claims 1-4, characterized in that: Includes the following steps, Ball milling: SiC and TiAl alloys are ball milled to obtain a mixed powder; Hot pressing sintering: The mixed powders are hot pressed and sintered to obtain a TiAl-based composite material preform; Encased hot forging: hot forging the billet by encasing it in a sleeve; Heat treatment: The cladding body is subjected to annealing heat treatment, followed by furnace cooling.
6. The method according to claim 5, characterized in that: The ball milling process involves mixing powders under argon protection, with a ball-to-powder ratio of 1:5, and the grinding balls are made of stainless steel.
7. The method according to claim 5, characterized in that: The hot pressing sintering is carried out under an argon atmosphere, at a temperature of 1250–1300°C, a holding time of 2–5 hours, and a pressure of 20–50 MPa.
8. The method according to claim 5, characterized in that: The hot forging temperature of the sheath is 1250-1300℃, and the deformation is 30%-70%.
9. The method according to claim 5, characterized in that: The heat treatment involves holding the temperature at 800–1000°C for 2 hours.
Citation Information
Patent Citations
TiAl / Ti3SiC2 composite plate material and preparation method thereof
CN104057667A
Ti3AlC2-SiC phase cooperative reinforcement Ni-based composite material and manufacturing method thereof
CN105463225A